Growth and Population Parameters of Panulirus penicillatus and Panulirus homarus in Labangka Tidal Waters, Indonesia - Evron Asrial; Erwin Rosadi; Hamid Hamid; Muhammad Ichsan; Ruly Isfatul Khasanah; Naning Dwi Sulystyaningsih; Agustin Dwi Sumiwi; Najiah Khalisah (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight • Utilization, Growth, and Population of Bullet Tuna (Auxis rochei Risso 1810) in Indian Ocean Southern Sumbawa (2020) • Eligibility Status Kawakawa (Euthynnus affinis Cantor, 1849) from Lombok Strait and Indian Ocean Southern Sumbawa (2020) • Biological Aspect of Parent Candidate of White-spotted Rabbitfish (Siganus canaliculatus) from Serewe Bay, Lombok Timur District (2020) • Study of Sustainability in Management of Malabar Blood Snapper Fisheries in the Indian Ocean Coastal Waters, Sumbawa Regency (2020) • Growth Rate and Survivorship of Acropora sp. Fragments that Transplanted on the Artificial Substrate Made from Fly Ash and Bottom Ash (2020) • Reproductive Biological Aspect of Panulirus penicillatus in Sumbawa Island Waters, Indonesia (2019) • Fisheries Resource Status of Spiny Lobster Panulirus penicillatus in Labangka Waters, South Sumbawa, Indonesia (2019) • Growth Rate of Acropora formosa Coral Fragments Transplanted on Different Composition of Faba Kerbstone Artificial Reef (2019) • Agribusiness of Edible Jellyfish Crambione mastigophora in Saleh Bay, NTB: Implementation of Sustainable Fisheries (2019)